Predictors for the utilization of community support systems against intimate partner violence among married women living with HIV in southwestern Uganda—A cross sectional study - Muteesasira, Edward; Akampumuza, Davis; Abaho, Dismus; Nuwasasira, Lillian; Kumakech, Edward (Plos one, 2024)
Background: Intimate partner violence (IPV) disproportionately affects married women living with HIV (MWLHIV), resulting in undesirable human rights, socio-economic, mental, maternal, and child health consequences. Community Support systems against Violence (CoSaV) are widely available and promising public and voluntary resources for the prevention and mitigation of IPV but are poorly investigated. We set out to identify the predictors for the utilization of the CoSaV among the MWLHIV. Methods: This was a quantitative cross-sectional study conducted among 424 consecutively sampled MWLHIV attending the Antiretroviral Therapy (ART) clinic at Kabale Regional Referral Hospital in southwestern Uganda in April 2021. Using an interviewer-administered questionnaire, data were collected on the participant’s socio-demographic characteristics, exposure to IPV, awareness about the CoSaV, perceptions about the quality, accessibility and challenges in accessing the CoSaV and the utilization. Modified Poisson regression model was used to identify the predictors for the utilization of CoSaV using the Statistical Package for Social Sciences (SPSS) version 23.0. Results: The mean age of the 424 participants in the study was 39.5±10.2 years. More than half of the participants 51.9% (220/424) reported exposure to any IPV. Utilization of any CoSaV was found to be above average at 58.3% among the participants. The formal support police, local government leaders, health workers and counselors) were more frequently utilized compared to the informal support (family, relatives and friends). Utilization of any CoSaV was higher among the women who were aware of the CoSaV and also those who were exposed to violence. Accessibility was identified as an independent predictor for utilization of any CoSaV. Conclusions: Intimate partner violence (IPV) was prevalent among MWLHIV in southwestern Uganda. However, the utilization of any CoSaV was suboptimal. The formal CoSaV were more frequently utilized than the informal support systems. Accessibility was an independent predictor for utilization of any CoSaV. There is need to improve access in order to increase the utilization of the CoSaV and contribute to the attainment of sustainable development goal 5.2.1 and end violence against women
Keywords: Intimate partner violence; Community Support systems against Violence; Married women; Uganda; HIV